Oto-tricho-tussia: An Unexpected Cause of Cough - Castro, Rebecca A.; Zalvan, Craig H.; Berzofsky, Craig (Case Reports in Otolaryngology, 2020)
Chronic cough is a frequently encountered condition with multiple etiologies. In patients with neurogenic chronic cough, peripheral laryngopharyngeal hypersensitivity of the vagus nerve stimulates the cough reflex. We present three cases of “Oto-tricho-tussia,” describing hair within the ear canal stimulating Arnold’s branch of the vagus nerve and triggering the urge-to-cough. All three patients experienced significant improvement or complete resolution of their cough symptoms after removal of the hair resting on their tympanic membrane and external auditory canal. We encourage ear canal examination and promotion of proper ear cleaning habits as this is an easily treatable consideration for the cause of chronic cough.